Fluctuations of ionizing particle track structure and energy resolution of scintillators - Gektin, A.V.; Vasil'ev, A.N. (Functional Materials, 2017)
The work is devoted to the study of fluctuations in ionizing particle track to the energy resolution deterioration. Reasons of deterioration of energy resolution of scintillators due to relatively rare events of production of high-energy Auger and delta-electrons are discussed in terms of different decay from regions with different concentration of excitations in track region. The model allows to assume that decay time changes reflect track non-uniformity and following energy resolution changes. The shallow traps which change the mobility of charge carriers could influence the long components of the decay and therefore modify the input to scintillation signal from regions with low concentration of excitations. This effect could be significant in deterioration of energy resolution of scintillators.